ANALISIS EFEKTIVITAS PEMBELAJARAN VIRTUAL DALAM PEMBENTUKAN KARAKTER DI SEKOLAH DASAR DAN PERGURUAN TINGGI - Rahman, Hardianto; Mytra, Prima; Bahar; Yusuf, Faidah; Syamsuddin, Afdal Fatawuri (Jurnal Pendidikan Dasar dan Keguruan, 2023)
The learning process is experiencing development and improvement. Various offers and choices of teachers appeared to carry out the learning process. One of them is by carrying out the learning process virtually. Every learning process certainly shapes the character of students. In this study, researchers wanted to reveal the character that was formed in students through a virtual learning process. The research method used is descriptive research. The results show that the virtual learning process can be carried out efficiently, but it is less effective in building character in students. The decrease in good character and the increase in bad character is the conclusion of this study.